A Critical Examination of Length of Stay in Autologous Breast Reconstruction: A National Surgical Quality Improvement Program Analysis. Issue 1 (30th September 2020) - Kotha, Vikas S.; Abadeer, Andrew I.; Amdur, Richard L.; Song, David H.; Fan, Kenneth L.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: This study aims to use the National Surgical Quality Improvement Program database to identify factors associated with extended postoperative length of stay after breast reconstruction with free tissue transfer. Methods: Consecutive cases of breast reconstruction with free tissue transfer were retrieved from the National Surgical Quality Improvement Program (2005 to 2017) database using CPT code 19364. Extended length of stay (dependent variable) was defined as greater than 5 days. Results: Nine thousand six hundred eighty-six cases were analyzed; extended length of stay was noted in 34 percent. On regression, patient factors independently associated with extended length of stay were body mass index (OR, 1.5; 95 percent CI, 1.2 to 1.9; p < 0.001), diabetes (OR, 1.3; 95 percent CI, 1.1 to 1.6; p = 0.003), and malignancy history (OR, 1.9; 95 percent CI, 1.22 to 3.02; p = 0.005). Operation time greater than 500 minutes (OR, 3; 95 percent CI, 2.73 to 3.28; p < 0.001) and immediate postmastectomy reconstruction (OR, 1.7; 95 percent CI, 1.16 to 2.48; p < 0.001) conferred risk for extended length of stay. Bilateral free tissue transfer was not significant. Operations performed in 2017 were at lower risk (OR, 0.2; 95 percent CI, 0.06 to 0.81; p = 0.02) for extended length of stay. Reoperation is more likely following operative transfusion and bilateral free tissue transfers, but less likely following concurrent alloplasty. Given a known operation time (minutes), postoperative length of stay (days) can be calculated using the following equation: length of stay = 2.559 + 0.003 × operation time. Conclusions: This study characterizes the risks for extended length of stay after free tissue transfer breast reconstruction using a prospective multicenter national database. The result of this study can be used to risk-stratify patients during surgical planning to optimize perioperative decision-making. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.